Disclaimer: I ended up finding what's asked for in the reverse order (e)-(a).
At time
, the horizontal position
and vertical position
of the ball are given respectively by
![x = v_i \cos(\theta_i) t](https://img.qammunity.org/2023/formulas/physics/college/16seobgjmu1ip7vioqf2myftwahs0er94o.png)
![y = v_i \sin(\theta_i) t - \frac g2 t^2](https://img.qammunity.org/2023/formulas/physics/college/pkipt5b5e716uzntab5r58zfzm72g4735y.png)
and the horizontal velocity
and vertical velocity
are
![v_x = v_i \cos(\theta_i)](https://img.qammunity.org/2023/formulas/physics/college/geaf14121ggzg5jdi2nng0xzfhgwcz9fbi.png)
![v_y = v_i \sin(\theta_i) - gt](https://img.qammunity.org/2023/formulas/physics/college/gpjfbhkxrdibpu9bao4i3x0v0z43pvz8ze.png)
The ball reaches its maximum height with
. At this point, the ball has zero vertical velocity. This happens when
![v_i \sin(\theta_i) - gt = 0 \implies t = \frac{v_i \sin(\theta_i)}g](https://img.qammunity.org/2023/formulas/physics/college/vz3qogieify6am38wbkm84qw54qo3adnry.png)
which means
![y = \frac R6 = v_i \sin(\theta_i) * \frac{v_i \sin(\theta_i)}g - \frac g2 \left(\frac{v_i \sin(\theta_i)}g\right)^2 \\\\ \implies R = \frac{6{v_i}^2 \sin^2(\theta_i)}g - \frac{3{v_i}^2 \sin^2(\theta_i)}g \\\\ \implies R = \frac{3{v_i}^2 \sin^2(\theta_i)}g](https://img.qammunity.org/2023/formulas/physics/college/gzpy7gj5kh6unhhojbpo5x7y15m2acnj8w.png)
At the same time, the ball will have traveled half its horizontal range, so
![x = \frac R2 = v_i \cos(\theta_i) * \frac{v_i \sin(\theta_i)}g \\\\ \implies R = \frac{2{v_i}^2 \cos(\theta_i) \sin(\theta_i)}g](https://img.qammunity.org/2023/formulas/physics/college/sd0m8uuj72thuzdxwg5ltqhfebj6mjy7br.png)
Solve for
and
:
![\frac{3{v_i}^2 \sin^2(\theta_i)}g = \frac{2{v_i}^2 \cos(\theta_i) \sin(\theta_i)}g \\\\ \implies 3 \sin^2(\theta_i) = 2 \cos(\theta_i) \sin(\theta_i) \\\\ \sin(\theta_i) (3\sin(\theta_i) - 2 \cos(\theta_i)) = 0](https://img.qammunity.org/2023/formulas/physics/college/8obrp80twhyizyrh7il2ol06khhezmbf16.png)
Since
, we cannot have
, so we're left with (e)
![3 \sin(\theta_i) - 2\cos(\theta_i) = 0 \\\\ \implies 3 \sin(\theta_i) = 2\cos(\theta_i) \\\\ \implies \tan(\theta_i) = \frac23 \\\\ \implies \boxed{\theta_i = \tan^(-1)\left(\frac23\right) \approx 33.7^\circ}](https://img.qammunity.org/2023/formulas/physics/college/nn5lnvgzrdfn8cm0u2nhxei0t6qofsen7v.png)
Now,
![\cos\left(\tan^(-1)\left(\frac23\right)\right) = \frac3{√(13)}](https://img.qammunity.org/2023/formulas/physics/college/y0r2zj6qh08kzujamjsla9mwy8q66pnmiw.png)
![\sin\left(\tan^(-1)\left(\frac23\right)\right) = \frac2{√(13)}](https://img.qammunity.org/2023/formulas/physics/college/rbuk55842ak59jpi2rpwmmnq04decr2hkr.png)
so it follows that (d)
![R = \frac{2{v_i}^2 *\frac3{√(13)} * \frac2{√(13)}}g \\\\ \implies {v_i}^2 = (13Rg)/(12) \\\\ \implies \boxed{v_i = \sqrt{(13Rg)/(12)}}](https://img.qammunity.org/2023/formulas/physics/college/9de8yjpuvsc8s76dw7bai4728r0qfwlqr1.png)
Knowing the initial speed and angle, the initial vertical component of velocity is (c)
![v_y = \sqrt{(13Rg)/(12)} \sin\left(\tan^(-1)\left(\frac23\right)\right) \\\\ \implies v_y = \sqrt{(13Rg)/(12)} * \frac2{√(13)} \\\\ \implies \boxed{v_y = \sqrt{\frac{Rg}3}}](https://img.qammunity.org/2023/formulas/physics/college/tr0f5a6oy8b5y6blewakq9mz7e91nu74hg.png)
We mentioned earlier that the vertical velocity is zero at maximum height, so the speed of the ball is entirely determined by the horizontal component. (b)
![v_x = \sqrt{(13Rg)/(12)} * \frac3{√(13)} \\\\ \implies v_x = (√(3Rg))/(2)](https://img.qammunity.org/2023/formulas/physics/college/nx8ijsvxatr2pfugwsynebf9gf3wqvn4tn.png)
Then with
, the ball's speed
is
![v = \sqrt{{v_x}^2 + {v_y}^2} \\\\ \implies v = v_x \\\\ \implies \boxed{v = \frac{√(3Rg)}2}](https://img.qammunity.org/2023/formulas/physics/college/aqxq0dctht6chi8c4t5y5jp1xee1dpq4o5.png)
Finally, in the work leading up to part (e), we showed the time to maximum height is
![t = \frac{v_i \sin(\theta_i)}g](https://img.qammunity.org/2023/formulas/physics/college/k7ewv3kb1wvxu611afyf3bxmkfi9j115g8.png)
but this is just half the total time the ball spends in the air. The total airtime is then
![2t = \frac{2 * \sqrt{(13Rg)/(12)} * \frac2{√(13)}}g \\\\ \implies 2t = 2\sqrt{\frac R{3g}}](https://img.qammunity.org/2023/formulas/physics/college/yg6coz5bvy8pw0wzelccurvwppk3aa3lzm.png)
and the ball is in the air over the interval (a)
![\boxed{0 < t < 2\sqrt{\frac R{3g}}}](https://img.qammunity.org/2023/formulas/physics/college/vpxvtlb839e6gphhp97pfcibr60oi6x76u.png)